Dolomitin borakslı ortamındaki flokülasyon davranışı - Kısmet, Hande (Fen Bilimleri Enstitüsü, 1996)
Eskişehir Kırka* daki tinkal cevheri Dünya1 nın en büyük boraks yatağını oluşturmaktadır. Ana bileşeni boraks dekahidratın yanısıra tinkal cevheri, yatağın yerine bağlı olarak % 20-45 civarlarında suda çözünmeyen maddeler de içermektedir. Bu maddelerin, yine yatağın yerine bağlı olarak değişen miktarlarda dolomit ve montmorillonit cinsi kil minerallerinden oluştuğu bilinmektedir. Tinkal cevherinden; bor tuzlan üretiminde cevherden gelen bu suda çözünmeyen maddelerin boraks çözeltilerinden ayrılmaları flokülasyon yöntemi ile gerçekleştirilmektedir. Dolomit- montmorillonit kanşımlanmn flokülasyonunda; dolomit içeriğinin artması ile flokülasyon kötüleşmekte, hatta bazı koşullarda mümkün bile olmamaktadır. Bu çalışmada, sadece dolomitin bor tuzlan üretim koşullarında flokülasyonu incelenerek, flokülasyon mekanizmasının belirlenmesi ve böylece dolomit- montmorillonit kanşımlanm daha iyi floküle edebilmek için gereken koşulların, belirlenmesi amaçlanmıştır. Deneylerde farklı boraks içerikli çözeltilerde (% 0; 3; 8; 15; 30) 30 g/l dolomit içerecek şekilde hazırlanan süspansiyonların farklı sıcaklıklarda (35, 65 ve 95 °C) ve çeşitli yükteki sentetik polimerler ile flokülasyonu yapılmış ve flokülan sarfiyatına bağlı olarak elde edilen çözeltilerin bulanıklık değişimleri saptanmıştır. Çalışmada elde edilen en önemli sonuç, dolomitin flokülasyon mekanizmasının dolomit ve montmorillonit kanşımlannınkinden tamamen farklı olmasıdır. Şöyle ki negatif yüzey yükü taşıyan dolomit ve montmorillonit taneciklerine iyonik olmayan veya anyonik yapıdaki polimerlerin adsorpsiyonu ağırlıklı olarak hidrojen köprüleri üzerinden gerçekleşmektedir. Buna karşılık negatif yük taşıyan dolomit tanecikleri üzerine iyonik olmayan veya anyonik polimerler adsorbe olmamakta, sadece katyonik yapıdaki polimerler elektriksel çekim kuvvetleri ile adsorbe olmaktadır.

Tincal ore in Kırka- Eskişehir(Turkey) is the largest borax deposit of the World. The main constituent being water-soluble borax decahydrate, tincal ore contains 20-45% of water insoluble materials which consist mainly of dolomite and montmorillonite in varying proportions. In conventional beneficiation process, a large part of these impurities are removed from the ore by washing it at ambient temperature with dilute solution. Tincal concentrate thus produced is dissolved in dilute borax solution at high temperature and the rest of the water insoluble materials are separated from the concentrated borax solution by flocculation in order to obtain a clear solution for the crystallization of borax deca and pentahydrates. The flocculation operation is the most important step of the whole process, because inefficient flocculation can cause problems such as contamination of the product with impurities, a loss of yield and environmental pollution. In a previous work, in which flocculation of dolomite- montmorillonite during the productions of borax compounds was investigated, it was determined that the dolomite content of the water insoluble materials was an important parameter effecting the flocculation, and turbidities of supernatants obtained from flocculations increased with the increase of the dolomite content of the water insoluble materials. In this study, flocculation behaviour of dolomite, instead of dolomite-montmorillonite mixtures was investigated under the conditions simulated to the productions of tincal concentrate, borax deca and pentahydrate, in order to evaluate the flocculation mechanism of dolomite in borax solutions. Thus it can be possible to enhance the flocculation efficiency of tincal slimes by an surface modification of dolomite particles. The dolomite sample used in the study was obtained from Marmara Island. The chemical composition of the sample are given in Table 1. IX Various polymeric flocculant used in the study are listed in Table 2. All flocculation experiments were performed using a Jar Test apparatus modified by a thermostated jacked to carry out the flocculation at different temperatures. Suspensions of 30 g/1 solid density were prepared in borax solutions of known concentrations and the mixtures were agitated at 130 rpm for 30 minutes. 0.05 % solutions of flocculants were added and the suspensions were further agitated for floe formation for 1 minute. After being allowed to settle for 10 minutes, the turbidities of supernatants were measured with the Hach Turbidimeter. The parameters affecting the flocculation of dolomite were chosen as the type of flocculant, the temperature and the borax concentration of the suspension. Effect of the type of flocculant on flocculation Suspensions of dolomite in distilled water and 3% borax solution were flocculated with polyethylenoxide, non-ionic and anionic polyacrylamide and catiomc acrylamide- 2-propen amide copolymer. Even though polyethylenoxide was reported to be used for the flocculation of dolomite in distilled water in the literature we could be able to flocculate the dolomite with both of polyethylenoxide and non-ionic and anionic polyacrylamides. Instead of non-ionic and anionic flocculant, cationic polyacrylamide flocculants were flocculated easily the dolomite in both of distilled water and 3% borax solution. This means that adsorption of polyelectrolytes onto the dolomite surface is through the electrostatic attraction. Since charged particles are stabilized by electrical repulsion, the adsorption of oppositely charged polymers could reduce or eliminate this repulsion and caused flocculation simply for this reason. The restabilization of particles by excess polymer could then be a result of charge reversal (e.g. negative particles could become positively charged by the adsorption of excess cationic polymer). Effect of the temperature on flocculation The flocculation results of dolomite in distilled water and 3% borax solution at 35 and 65 °C with 20% cationic (FO4290) flocculant were compared in Figure 1. For the suspension in distilled water, increasing the temperature from 35 °C up to 65 °C had as positive effect on the flocculation. For the suspension in 3% borax solution the same increase in temperature caused an increase of turbidity of supernatant. a) 250 0.2 0.4 0.6 0.8 1 1.2 Amount of flocculant ( g / kg dolomite ) 1.4 b) 250 200 - g 150 I I 100 50 0 0.2 0.4 0.6 0.8 1 1.2 1.4 Amount of flocculant ( g / kg dolomite ) Figure 1. Turbidities of supernatant solutions at two different flocculation temperatures a) Distilled water b) 3% Na2B407 XI It is generally thought that increase in temperature improves flocculation, although this is not always the case, since a charge in temperature will exert different effects in different systems. Instead of 20% cationic flocculant (FO4400) was used for the flocculation of suspensions in 3% borax solution at 35 and 65 °C and the results obtained at 65 °C were better than those at 35 °C. This means that by increasing the temperature the surface charge of dolomite particle became more negative. Effect of the borax concentration of suspensions As an example of the effect of the borax concentration, the result obtained for the flocculations of dolomite in 0, 3, 8 and 15% borax solutions with 30% cationic flocculant (FO4400) at 65 °C are given in Figure 2. 250 200 150 t ?S loo 50 ? %0NaaBi,Ot ? "/oŞNa^O? ? % 3 Na^CH. %15NagBi,Q? 0.2 0.4 0.6 0.8 1 Amount of flocculant ( g / kg dolomite ) 1.2 1.4 Figure 2. Effect of borax concentration on the turbidity of supernatant solution Increasing the borax concentration of suspensions from 0 to 15% had a negative effect on the flocculation, and the optimal charge density of flocculants increasing the borax concentration. This means that the charge of dolomite surface became more negative when the borax concentration of the suspension increased. In Figure 3, effect of the charge density of flocculant can be seen for the flocculation of dolomite in 8% borax solution at 65 °C. xu 250 200 150 t Ü 100 50 ? FO4290(%20) AFO4400(%30) ^04490(0/0 40) BFCMeSOC/oSS) 0.2 0.4 0.6 0.8 1 1.2 Amount of flocculant ( g / kg dolomite ) 1.4 Figure 3. Turbidities of supernatant solutions after flocculation of dolomite with various flocculants The most important results of this study are those that the flocculation mechanism of dolomite is the charge neutralization between the negative particles and positive charged polyelectrolytes, and the charge of dolomite surface is becoming more negative with increasing the temperature and the borax concentration of the suspension. The practical application of these results were tryied by flocculating of dolomite-montmorillonite mixture under the conditions of tincal concentrate, borax decahydrate and borax pentahydrate productions. For this purpose, the suspensions of the water insoluble material of tincal ore which contains 22.5% montmorillonite and 77.5% dolomite were prepared in 15% and 30% borax solutions, and were flocculated at 95 °C with polyethylene oxide and polyacrylamides. Before flocculations, a small amounts of cationic flocculant were added to the suspensions for the charge neutralization of dolomite, and then the required amount of non-ionic or anionic flocculants were added. The turbidities of supernatants were low when compared with the results obtained without charge neutralization. This means that charge neutralization before flocculation can cause an increase in the flocculation efficiency.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Boraks; Dolomit; Flokülasyon; Borax; Dolomite; Flocculation